Synthesis and characterization of Sn reinforced Al-Cu-Fe quasicrystalline matrix nanocomposite by mechanical milling - Shadangi Y.; Shivam V.; Singh M.K.; Chattopadhyay K.; Basu J.; Mukhopadhyay N.K. (My University, 2025)
The influence of mechanical milling (MM), primarily on microstructure and phase evolution in Al62.5Cu25Fe12.5 (at%) quasicrystalline (IQC) matrix reinforced with varying volume fraction of Sn has been investigated by means of X-ray diffraction (XRD), scanning & transmission electron microscopy (SEM and TEM) and differential scanning calorimetry (DSC) methods. It was observed that with increasing the milling duration, the IQC phase transforms to crystalline B2 phase [Al (Cu, Fe) and Pm3 m, a = 0.29 nm]. In SEM and TEM analysis, it was found that both IQC and Sn particles are refined during MM. The XRD and TEM results confirm the formation nanostructured matrix consisting of nanocrystalline B2 phase along with minor IQC phase reinforced with ultrafine grained Sn particles after 40 h of MM. The STEM-EDS results show a homogenous distribution of elements (Al, Cu, Fe). The Sn particles were immiscible in a matrix consisting of B2 and IQC phase as indicated by XRD and TEM investigations. © 2019 Elsevier B.V.